Algorithms and Data Structures for Numerical Computations with Automatic Precision Estimation (Indian Journal of Artificial Intelligence and Neural Networking (IJAINN), 2024)
We introduce data structures and algorithms to count numerical inaccuracies arising from usage of floating numbers described in IEEE 754. Here we describe how to estimate precision for some collection of functions most commonly used for array manipulations and training of neural networks. For highly optimized functions like matrix multiplication, we provide a fast estimation of precision and some hint how the estimation can be strengthened.